KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 4 PARIAMAN - Putri, Diana; R., Syahrul (Universitas Negeri Padang, 2019)
ABSTRACT This research focus on the describing skill correlation of reading understanding and skill text writing report observation results of the seventh grade students of SMP Negeri 4 Pariaman. This type of research is quantitative research with correlational methods. The sample of this research is students of SMP Negeri 4 Pariaman amounted 42 students. The data of this research are the score of the reading comprehension skill test results and the score of the test results in the writing skills of the report text of the seventh grade students of SMP Negeri 4 Pariaman. Based on the research, it can be concluded that there is a significant relationship between reading skills understanding of the report writing skills in the text of the observation results of seventh grade students of SMP Negeri 4 Pariaman. Based on analysis data and discussion, there are several conclusion obtained. First, the skill of Report Writing Text Results of Observation of seventh grade Students of SMP Negeri 4 Pariaman is in good qualification (80.95). Second, the skill of reading Comprehension of seventh grade Students of SMP Negeri 4 Pariaman is in good qualification (80.36). Kata kunci: Korelasi, Membaca Pemahaman, Menulis, Teks Laporan Hasil Observasi